2006
DOI: 10.1068/p5506
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Waist: Hip Ratio are Not Enough to Characterise Female Attractiveness

Abstract: The assessment of characteristic body features of Miss Poland beauty contest finalists compared with the control group, can contribute to recognising the contemporary ideal of beauty promoted by the mass media. The studies of Playboy models and fashion models conducted so far have been limited to the following determinants of attractiveness: body mass index, waist:hip ratio, and waist:chest ratio, which only partially describe the body shape. We compared 20 body features of the finalists of Miss Poland 2004 be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 9 publications
3
14
0
Order By: Relevance
“…The preeminent role of waist size in female attractiveness is consistent with findings from the relatively few studies that have considered it as a separate variable (Brody, 2004;Brody & Weiss, 2013;Brooks et al, 2010Brooks et al, , 2015Crossley et al, 2012;Forestell et al, 2004;Grundl et al, 2009;Horvath, 1981;Pokrywka et al, 2006;Prantl & Grundl, 2011;Rilling et al, 2008;Rozmus-Wrzesinska & Pawlowski, 2005). In particular, it is congruent with the findings of Brooks, Shelly, Jordan, and Dixson (2015) who found that waist size was the parameter that changed the most as participants in a selection experiment ''evolved'' figures with increasing attractiveness.…”
Section: Waist Size Explains the Relationship Of Whr Bmi And Hip Sisupporting
confidence: 89%
See 1 more Smart Citation
“…The preeminent role of waist size in female attractiveness is consistent with findings from the relatively few studies that have considered it as a separate variable (Brody, 2004;Brody & Weiss, 2013;Brooks et al, 2010Brooks et al, , 2015Crossley et al, 2012;Forestell et al, 2004;Grundl et al, 2009;Horvath, 1981;Pokrywka et al, 2006;Prantl & Grundl, 2011;Rilling et al, 2008;Rozmus-Wrzesinska & Pawlowski, 2005). In particular, it is congruent with the findings of Brooks, Shelly, Jordan, and Dixson (2015) who found that waist size was the parameter that changed the most as participants in a selection experiment ''evolved'' figures with increasing attractiveness.…”
Section: Waist Size Explains the Relationship Of Whr Bmi And Hip Sisupporting
confidence: 89%
“…However, the measurements of beauty contestants, which are verified, are remarkably similar to those of Playmates (Hong et al, 2009;Pokrywka et al, 2006;Singh, 1993a).…”
Section: Limitationsmentioning
confidence: 79%
“…Because the middle value of the WHR scale (.60–.85) was .725, and the average WHR for young Polish women is equal to or only slightly higher than this (Jasieńska et al, 2004; Pawłowski & Grabarczyk, 2003; Pokrywka, Čabrić, & Krakowiak, 2006), we tested whether the most preferred values differed significantly from .725. According to the one-sample t test, only values for Color18, t (39) = 3.12, p  = .003, and Color21 series, t (39) = 2.53, p  = .015, differed significantly from and was lower than .725.…”
Section: Resultsmentioning
confidence: 99%
“…This difference amounts to .04, which is about 1 SD (Pawłowski & Grabarczyk, 2003; Pokrywka et al, 2006) and means, for example, that a woman with WHR of .70 would possess the width-based WHR of about .66. The factor of 1.055 provided by Smith et al (2007) leads to very similar conclusions (.66 × 1.055 = .70).…”
Section: Discussionmentioning
confidence: 99%
“…Much scholarly work has focused, for example, on the relative importance of body shape and weight to women's physical attractiveness (for reviews, see Swami & Furnham, 2006, 2007; Swami, 2006, 2007). However, body size alone does not sufficiently define the ideal female body, and other body proportion measures may also be important (Pokrywka, Čabrić, & Krakowiak, 2006).…”
mentioning
confidence: 99%